Iketes - Ioannou, Stavros (Greece : Greek Film Center, 2006)
A fishing boat laden with illegal immigrants sets sail from Izmir and is shipwrecked that very night on the cliffs of Evia. Most of them clamber up the rocks but some drown. Crammed into makeshift quarters – an abandoned olive press – for three months, the immigrants give voice to their dreams. All of them young men, the children of war from Afghanistan, Kashmir, Sri Lanka, Pakistan, Iran, Turkey and China, are supplicants, begging not to be sent back, not to find themselves living in the hell of war and poverty once more.
Keywords: Documentary films